2021
DOI: 10.24002/kinerja.v25i2.4593
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Service Quality on Satisfaction in E-Banking Services- An Empirical Study

Abstract: Customer satisfaction is now taking as a core issue in all the service oriented sectors and especially, banking institutions have considered this as a base point due to heavy competition and proffering higher services through digital and electronic mode. Even though they have offered better service, satisfaction level towards these E-banking services among the customers is not dynamic because of  not having adequate knowledge among them  in using these services which clearly reflected the under usage of custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Each bank is required to pay consideration on increasing the availability by delivering service. It will result in improving its client service by means of updated and modern technology (Vijayanand & Kumar, 2021). The process of clients' relation-building is related to automating SQ.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each bank is required to pay consideration on increasing the availability by delivering service. It will result in improving its client service by means of updated and modern technology (Vijayanand & Kumar, 2021). The process of clients' relation-building is related to automating SQ.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…To become a successful company, SQ is obligatory to satisfy its clients. If services are deficient, the rate of clients' deflection will be augmented on account of other offered services by competitors (Vijayanand & Kumar, 2021). The gap exists in the literature on account of limited research in exploring E-banking post-adoption clients' behaviour (Toqeer et al, 2021).…”
Section: Nexus Among Obsq Cpv and Cpbimentioning
confidence: 99%
“…The correlation result for 390 respondents shows that there is a positive correlation between all attributes of e-banking services and CS. Vijayanand and Kumar (2021) conducted an empirical study to analyze the impact of SQ on satisfaction in e-banking services in public sector banks in India, for a simple random sample of (667) clients and concluded that the various e-banking factors (Responsiveness, Convenience, and Security) and demographic variables have a positive correlation on CS. Khan and Alhumoudi (2022) presented the structural equation model approach, using CS as a mediator to measure the performance of e-banking services for a stratified random sample.…”
Section: Introductionmentioning
confidence: 99%